Transnational knowledge transfer: the context of cross-border and local firms in private real estate collaborations in Sub-Saharan Africa - Ndlovu, Pride (My University, 2022)
Foreign firms have traditionally been utilized by governments in host countries to execute complex projects and were coerced by legislative requirements in public sector to partner with local firms to transfer knowledge. Traditionally, these joint ventures have been unsuccessful in transferring knowledge to local partners. But still international joint ventures continue to be used in the private sector as an entry strategy to new markets, without any legislative requirement coercing partners to form a joint venture. The study aims to investigate these private sector joint ventures forming a transnational knowledge network and evaluate the strategies they use to interact within the network and how they work on differences to create new knowledge used to achieve project goals. An integrated theoretical framework comprising of embeddedness theory, social capital theory, knowledge creation theory and the model of transnational public sector knowledge networks was adopted, and this model was further tested for its relevance and applicability in private real estate sector. The qualitative research methodology was used with multiple case studies of local firms and cross-border firms in a transnational joint venture in Sub-Saharan Africa (SSA). Data was collected through semi structured interviews, comprised of 11 cases, each using a purposive sampling of cross-border firm (SA firms) and a snowball sampling of local partner (spread out across the rest of SSA), making a total of 22 participants that were interviewed in the study. Documentary analysis of related documents for the transnational joint venture was perused. The data collected was analyzed using thematic qualitative data analysis techniques. The findings revealed that in order to reduce the differences that parties come to the network embedded in, continuous adapting, learning, transferring, integrating and innovation are continuously utilized by partakers as the five main generic principles or practices in a transnational knowledge network to create new knowledge, bridge differences and meet project goals. The study also revealed that the knowledge difference between local and cross-border partakers in private real estate was not severe and local firms had professional skill but lacked exposure and experience in executing a high-quality real estate asset that did not exist in their home country before. The study further identified the emergence of Welfare as a unique distance that exists in the context of SSA and this finding expands the transnational knowledge transfer model adding the tenth distance to it. This finding contributes to the literature and accentuates the significance of exploring the context of emerging countries.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2022